2017
DOI: 10.1371/journal.pone.0177917
|View full text |Cite
|
Sign up to set email alerts
|

Co-inheritance of glucose-6-phosphate dehydrogenase deficiency mutations and hemoglobin E in a Kachin population in a malaria-endemic region of Southeast Asia

Abstract: Glucose-6-phosphate dehydrogenase (G6PD) deficiency and hemoglobin E (HbE, β26 Glu-Lys) are two common red cell disorders in Southeast Asia. G6PD deficiency produces hemolytic anemia, which can be triggered by certain drugs or infections. HbE is asymptomatic or is manifested as microcytic, minimally hemolytic anemia. The association between G6PD deficiency and HbE is little understood. This study aimed to investigate G6PD deficiency and HbE in a Kachin ethnic group in the China-Myanmar border area. G6PD enzyme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 34 publications
2
20
0
Order By: Relevance
“…Additionally, one study observed high prevalence of HbE in highly malarious regions compared to the regions with a low incidence of malaria [94]. Recently, one study reported high prevalence of co-inheritance of HbAE and G6PD deficiency [95], which is another variant that provides protection against malaria and has gone through positive selection [96]. In addition, Deng et al pointed out that the time frame of HbE origination (between 1240 and 4440 years ago) [8] coincides with the origination of the most common G6PD variant in Southeast Asia, which had been affected by positive selection over the past 1500 years [97].…”
Section: Studies On the Association Between Hbe And Malariamentioning
confidence: 99%
“…Additionally, one study observed high prevalence of HbE in highly malarious regions compared to the regions with a low incidence of malaria [94]. Recently, one study reported high prevalence of co-inheritance of HbAE and G6PD deficiency [95], which is another variant that provides protection against malaria and has gone through positive selection [96]. In addition, Deng et al pointed out that the time frame of HbE origination (between 1240 and 4440 years ago) [8] coincides with the origination of the most common G6PD variant in Southeast Asia, which had been affected by positive selection over the past 1500 years [97].…”
Section: Studies On the Association Between Hbe And Malariamentioning
confidence: 99%
“…Heterozygous females who are G6PD deficient are genetic mosaics as an effect of X-chromosome inactivation; the abnormal cells of a heterozygous female can be as deficient for G6PD as similar to a G6PD-deficient male: consequently, such females can be vulnerable to the equivalent pathophysiological phenotype. While heterozygous females typically have less severe clinical presentations than G6PD-deficient males, yet some may develop severe acute hemolytic anemia [7,8] .…”
Section: Inheritance Patternsmentioning
confidence: 99%
“…About 140 mutations have been so far been reported, majority are single-base substitutions causing amino acid replacements. In rare cases, a second mutation may be present in cis point mutations range all over the entire coding region [7] .…”
Section: Genetic Mutations and Molecular Aspectsmentioning
confidence: 99%
See 1 more Smart Citation
“…The prevalence of HbE varies among populations; at the junction of Thailand, Laos and Cambodia, 50–60% of the human population are HbE carriers (7). In some ethnic groups residing along the China-Myanmar border, HbE prevalence is also high and almost reaches 40% (8, 9). Whereas there is particularly strong evidence to support that the HbS variant and α-thalassemias offer protection against severe malaria, evidence about HbE’s protection against malaria is less convincing (1, 10).…”
Section: Introductionmentioning
confidence: 99%